Cognitive function and neuroimaging correlates in a subjective cognitive decline population within a multimodal intervention supplemented with green tea extract (PENSA Study): Preliminary results of a voxel‐based morphometry study. (December 2021) - Lorenzo, Thais; Operto, Greg; Falcon, Carles; Cuenca, Aida; Forcano, Laura; Piera, Iris; Puig‐Pijoan, Albert; Soldevila‐Domenech, Natalia; Boronat, Anna; Knezevic, Iva; Fauria, Karine; Molinuevo, Jose; et al.
Abstract: Background: Multicomponent interventions including diet, physical activity and cognitive training have shown great potential to prevent cognitive decline in individuals at risk of developing the clinical stages of Alzheimer's disease (AD). The PENSA study is a clinical trial focused on the prevention of cognitive decline in individuals with subjective cognitive decline (SCD) who are also APOE ε4 carriers. It is based on a 12‐month multimodal intervention (nutritional, physical and cognitive) combined with epigallocatechin‐3‐gallate (EGCG), a natural flavanol and known synaptic plasticity booster. In this study, we sought for neuroimaging correlates of cognitive performance of the PENSA participants at baseline. Method: Twenty‐five (N=25) SCD participants of the PENSA Study at baseline (Table 1) with valid T1w and T2w MRI scans were included. They also underwent a neuropsychological assessment battery consisting of the modified Alzheimer Disease Cooperative Study Preclinical Alzheimer Cognitive Composite (ADCS‐PACC‐like) and additional cognitive performance scores obtained from (i) semantic verbal fluency, (ii) Boston Naming Test, (iii) digit span subtest, (iv) visual puzzle subtest and (v) the Montreal Cognitive Assessment. In addition, measurements of mental health, functionality, quality of sleep and quality of life perception have been assessed. T1w and T2w MRI scans were used to perform a multimodal segmentation of grey matter volumes (GMv) entered in the SPM12 voxel‐based morphometry (VBM) pipeline. Associations between test scores and GMv were sought (p<0.001) including age, sex, education and total intracranial volume as confounders. Result: A negative correlation was found between the Free and Cued Selective Reminding Test (FCSRT) performance and GMv in the left anterior cingulate gyrus, left medial temporal lobe, right and middle temporal gyrus and left medial orbital gyrus (Figure 1). The rest of comparisons did not survive the statistical significance threshold. Conclusion: Preliminary results show the expected pattern of negative associations between GMv and episodic memory performance, therefore suggesting that the PENSA study is recruiting the intended population of SCD individuals at risk of developing clinical stages of AD who could benefit from multimodal preventive interventions.